2012
DOI: 10.1021/jz201551e
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Competitive Electrocatalysts for Hydrogen Fuel Cells

Abstract: The large-scale application of one of the most promising clean and renewable sources of energy, hydrogen fuel cells, still awaits efficient and cost-effective electrocatalysts for the oxygen reduction reaction (ORR) occurring on the cathode. We demonstrate that truly rational design renders electrocatalysts possessing both qualities. By unifying the knowledge on surface morphology, composition, electronic structure, and reactivity, we solve that trimetallic sandwich-like structures are an excellent choice for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…As mentioned in Introduction, we select Au as the AE because it has a very high dissolution potential V diss (Au)=1.5 V/SHE which will ensure electrochemical stability of the systems. We also expect that a reactive MS will activate Au to the level favorable for ORR . To select MSs, first, we try to meet one of the important criteria for thermodynamic stability of the AE/MS structures, which is a low bond‐length mismatch between the AE and the MS. We found that Nb, Ta, Mo, and W meet this criterion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in Introduction, we select Au as the AE because it has a very high dissolution potential V diss (Au)=1.5 V/SHE which will ensure electrochemical stability of the systems. We also expect that a reactive MS will activate Au to the level favorable for ORR . To select MSs, first, we try to meet one of the important criteria for thermodynamic stability of the AE/MS structures, which is a low bond‐length mismatch between the AE and the MS. We found that Nb, Ta, Mo, and W meet this criterion.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, core‐shell designs continue being extensively explored, and a significant progress can be made in this direction if PGE‐based alloys in the core are replaced with less expensive materials. To achieve this goal, we have proposed early transition metals (ETM) as possible MS materials and noble metals as possible AEs . The advantages of ETMs are that they are inexpensive and highly abundant in Earth's crust and promote the thermodynamic stability of the AE/MS structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Nevertheless, it is also well known that the surfaces of bulk Au embody unparalleled cases of metal resistance towards forming compounds with highly electronegative atoms such as O, N, and C. The prime and simplest indication of the latter is undoubtedly the binding of atomic oxygen on metal surfaces. 5 In this regard, adsorption calorimetry and temperature-programmed desorption measurements [6][7][8][9][10][11][12][13][14][15] have confirmed that, among all transition metal surfaces, Au(111) forms the least stable bond with atomic oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The perspective given by the d-band model has been applied to understand the catalytic activity of a number of single-element and bimetallic 20,21 transition-metal surfaces 5,17,22 and has provided an essential tool for designing catalysts. 4,22 Nonetheless, there are critical inconsistencies between its predictions and experiment and/or ab initio calculations that involve adsorption on group-11 and group-10 metal surfaces. Below, we only focus on the cases relevant to the subject of this work.…”
Section: Introductionmentioning
confidence: 99%